Uncovering The Accounting Practices of The Rewang Tradition - Iwan Triyuwono; Lilik Purwanti; Melinda Ibrahim; Kartika Putri Kumalasari; Aryo Prakoso; Nanda Widaninggar; Ni Putu Riski Martini (Jurnal Reviu Akuntansi dan Keuangan, 2025)
Purpose: This study aims to uncover accounting practices in the Javanese rewang tradition, focusing particularly on the role of women in this traditional mutual assistance system. Methodology/approach: The research employs a qualitative descriptive approach conducted in Janti Village, Wates District, Kediri Regency. Data was collected through interviews, observation, and documentation from six key informants, including recipients and rewang assistance providers. Data analysis utilized qualitative analysis with source and method triangulation for validity testing. Findings: The study reveals that rewang accounting practices encompass two perspectives: providers record it as either an accounts receivable (expecting future reciprocation) or as an expense/donation (without expectation of return), while recipients view it as either a liability (obligation to reciprocate) or donation income (assistance without future obligations). Additionally, the research uncovers sophisticated value measurement systems based on duration, skills contributed, and event context, supported by informal documentation through collective memory and community records. Practical implications: The findings demonstrate how traditional mutual assistance systems can be understood through modern accounting frameworks while preserving their cultural essence. Originality/value: This study presents a novel approach by examining the traditional Javanese rewang practice through an accounting lens, particularly focusing on women's roles in maintaining social and cultural values.